(untitled) (Hematology Meeting Reports, 2009)
The existence of recurring and successful International Conference on Thrombosis and Hemostasis Issues in Cancer arises is due to the well-documented and frequent clinical association between malignancy and excessive thrombosis in humans. Unfractionated heparin (UFH) has been the classic anticoagulant of choice to treat cancer patients with thrombosis, and recent studies have indicated that UFH could be replaced by various low molecular weight heparins (LMWHs), which have several advantages for clinical use. Heparins are also the agent of choice in treating patients with classic Trousseau’s Syndrome (spontaneous migratory thrombophlebitis with microangiopathic symptoms, typically associated with mucin-producing carcinomas). Meanwhile, UFH has been shown to reduce tumor metastasis in many murine models. Also, retrospective and post-hoc analyses of clinical studies suggest that UFH and some LMWHs might improve outcomes in human cancer.